PENGARUH SOLVABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN (Studi Kasus Perusahaan Consumer Goods yang Terdaftar di BEI Tahun 2011-2015) - Eka Putri Septia Rini; Muhammad Agus Salim; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis research was aimed to investigate the influence of solvability,liquidity and firm size to profitability in the consumer goods company at BursaEfek Indonesia (BEI) period 2011-2015. The population of this research is everyconsumer goods company enlisted in the BEI at the year 2011-2015. The sampleswere obtained by using the purposive sampling method until only 27 companieswere qualified as samples. This research used secondary data and multipleregression analysis method.The result of this research shows that the variable of solvability hasnegative and significant effect to the profitability, the variable of liquidity hasnegative and insiginificant effect to the profitability, the variable of firm size hasnegative and significant effect to the profitability.Simultaneously variablesolvability, liquidity and firm size to profitability have significant influence onprofitability.Keywords: Profitability, Solvability, Liquidity, Firm Size